Spirulina plantesis flour supplementation to increase the growth and brightness of the color of Betta fish (Betta splendens) Regan, 1910 - Sutarjo Ganjar Adhywirawan; Prasetyo Dony; Handajani Hany; Diba Dalila Fara (BIO Web of Conferences)
The cultivation of ornamental fish has not yet reached an adequate level to consistently produce high color quality, which is a key determinant of the fish’s market value. This study aims to investigate the Effect of Spirulina platensis, which is believed to contain carotenoids that can enhance the color of freshwater ornamental fish, specifically Betta splendens. A quantitative approach using a Completely Randomized Design (CRD) experimental model was employed to test the hypothesis, with the results analyzed statistically and described in detail. The study found that treatment 2, involving a 1% concentration of Spirulina powder in artificial feed, resulted in the best increase in color intensity, as indicated by a more yellow and darker hue compared to the control, P3, and P4 treatments. The study suggests that future research should include a larger sample size to achieve optimal results.